2019
DOI: 10.1080/17938120.2019.1583508
|View full text |Cite
|
Sign up to set email alerts
|

Targeting debt in Lebanon: a structural macro-econometric model

Abstract: All rights reserved. No part of this publication may be reproduced in any form or by any electronic or mechanical means, including information storage and retrieval systems, without permission in writing from the publisher.The findings, interpretations and conclusions expressed in this publication are entirely those of the author(s) and should not be attributed to the Economic Research Forum, members of its Board of Trustees, or its donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The findings concluded that the level of debt is unsustainable in Pakistan. The heavy reliance on debt is observed by Anwer (2000), who reported that it is due to high dependency on the IMF and World Bank. High reliance on debt to correct the current account deficit makes it not sustainable and only increases financial vulnerability and recession that ultimately tends to reschedule debt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings concluded that the level of debt is unsustainable in Pakistan. The heavy reliance on debt is observed by Anwer (2000), who reported that it is due to high dependency on the IMF and World Bank. High reliance on debt to correct the current account deficit makes it not sustainable and only increases financial vulnerability and recession that ultimately tends to reschedule debt.…”
Section: Literature Reviewmentioning
confidence: 99%